Immune microenvironment spatial landscapes of tertiary lymphoid structures in gastric cancer - Yi Xie; Haoxin Peng; Yajie Hu; Keren Jia; Jiajia Yuan; Dan Liu; Yanyan Li; Xujiao Feng; Jian Li; Xiaotian Zhang; Yu Sun; Lin Shen; et al. (BMC Medicine)
Abstract Background Tertiary lymphoid structures (TLS) correlate with tumour prognosis and immunotherapy responses in gastric cancer (GC) studies. However, understanding the complex and diverse immune microenvironment within TLS requires comprehensive analysis. Methods We examined the prognostic impact of TLS within the tumour core (TC) of 59 GC patients undergoing immunotherapy. Multispectral fluorescence imaging was employed to evaluate variations in immune cell infiltration across different TLS sites among 110 GC patients, by quantifying immune cell density and spatial characteristics. We also generated a single-cell transcriptomic atlas of TLS-positive (n = 4) and TLS-negative (n = 8) microenvironments and performed spatial transcriptomics (ST) analysis on two samples. Results TLS presence in the TC significantly correlated with improved immune-related overall survival (P = 0.049). CD8+LAG-3−PD-1+TIM-3−, CD4+PD-L1+, and CD4+FoxP3− T cell densities were significantly higher in the TLS within TC compared to tumour and stromal regions. Immune cells within TLS exhibited closer intercellular proximity than those outside TLS. Five key density and spatial characteristics of immune cells within TLS in the TC were selected to develop the Density and Spatial Score risk model. Single-cell RNA sequencing revealed strong intercellular interactions in the presence of TLS within the microenvironment. However, TLS-absent environment facilitated tumour cell interactions with immune cells through MIF- and galectin-dependent pathways, recruiting immunosuppressive cells. ST analysis confirmed that T and B cells co-localise within TLS, enhancing immune response activation compared to cancer nests and exerting a strong anti-tumour effect. Conclusions TLS presence facilitates frequent cell-to-cell communication, forming an active immune microenvironment, highlighting the prognostic value of TLS.